Critical role of metabotropic glutamate receptor 4 in bone marrow-derived dendritic cells in the Th17 cell differentiation and the melanogenesis of B16 cells - Zhao,Guangming (2020)
Vitiligo is an acquired pigmentary disorder resulting from selective destruction of melanocytes. Emerging studies have suggested that T helper cell 17 (Th17) is potentially implicated in vitiligo development and progression. It was recently discovered that metabotropic glutamate receptor 4 (mGluR4) can modulate Th17-mediated adaptive immunity. However, the influence of mGluR4 on melanogenesis of melanocytes has yet to be elucidated. In the present study, we primarily cultured mouse bone marrow-derived dendritic cells (BMDC) and then knocked down and over-expressed mGluR4 using transfection. Transduced BMDC were co-cultured with CD4+ T cells and the expression of Th17-related cytokines were measured. The morphology and melanogenesis of B16 cells were observed after being treated with co-culture medium of CD4+ T cells and transduced BMDC. We found that mGluR4 knockdown did not affect the co-stimulatory CD80 and CD86 upregulation after lipopolysaccharide stimulation but did increase the expression of Th17-related cytokines, and further down-regulated the expression of microphthalmia-associated transcription factor (MITF) and the downstream genes, decreased melanin production, and destroyed the morphology of B16 cells. Conversely, over-expression of mGluR4 reduced the expression of CD80 and CD86, suppressed the production of Th17-related cytokines, increased the expression of MITF, and did not destroy the morphology of B16 cells. Our study confirmed that mGluR4 modulated the Th17 cell polarization and resulted in the alteration of melanogenesis and morphology of B16 cells. Collectively, these findings suggest mGluR4 might be a potent target involved in the immune pathogenesis of vitiligo.